Politik Dunia Arab Klasik dan Modern: Studi Kasus Kepemimpinan Ibnu Saud dan Husni Mubarak - Muhammad Irfan Maulana; Aulia Nur Rahma (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2022)
The Arab world is undergoing a transformation in leadership. Every powerful leader has characteristics in running the government politically. This study will examine the politics of the classical and modern Arab world by case studies on King Ibn Saud (Saudi Arabia) and King Husni Mubarak (Egypt). This research is a literature study that describes the character of the political system of Ibn Saud and Husni Mubarak. This study reveals that there are special characteristics that the two leaders have during their tenure. Ibn Saud smartly took advantage of the opportunity and got the world's attention with the Al Saud Clan's collusion politics and religious politics with Wahhabis. Husni Mubarak uses social media and technology to maintain power.